Chronic exposure to high altitude and the presence of coronary ectasia in patients with ST elevation myocardial infarction - Chacón Díaz, Manuel Alberto (2023)
Objective. To evaluate the association between chronic exposure to high altitude and the presence of coronary ectasia (CE) in patients with ST-segment elevation myocardial infarction (STEMI) treated in a highly specialized cardiovascular reference hospital in Peru. Materials and methods. Retrospective matched case-control study. The cases were patients with CE and controls without CE. The relationship between CE and chronic exposure to high altitude was evaluated considering intervening variables such as arterial hypertension, diabetes mellitus, dyslipidemia, smoking, and hematocrit values. Patients with chronic inflammatory pathologies, chronic obstructive pulmonary disease, and previous revascularization were excluded. Multivariate logistic regression was applied to obtain the OR value and their respective confidence intervals. Results. Eighteen cases and 18 controls were studied, most of them were men with an average age of 65 years. Thirty-six percent of the population came from high altitude; in this group 76.9% had coronary ectasia of the infarct-related artery. The mean hematocrit value was slightly higher in the high-altitude native (46 ± 7% versus 42 ± 5%, p=0.094). Multivariate conditional logistic regression did not find a significant relationship between exposure to high altitude and the risk of presenting CE (OR:6.03, IC95%: 0.30-118, p=0.236). Conclusions. In patients with STEMI, we found no association between chronic exposure to high altitude and coronary ectasia.